Assessing the capacity for mental manipulation in patients with statically-determined mild cognitive impairment using digital technology - Sheina Emrani; Melissa Lamar; Catherine C. Price; Satya Baliga; Victor Wasserman; Emily Matusz; Rod Swenson; Ganesh Baliga; David J. Libon (Open Exploration Publishing Inc., 2021)
Aims: Prior research employing a standard backward digit span test has been successful in operationally defining neurocognitive constructs associated with the Fuster's model of executive attention. The current research sought to test if similar behavior could be obtained using a cross-modal mental manipulation test. Methods: Memory clinic patients were studied. Using Jak-Bondi criteria, 24 patients were classified with mild cognitive impairment (MCI), and 33 memory clinic patients did not meet criteria for MCI (i.e. non-MCI). All patients were assessed with the digital version of the WRAML-2 Symbolic Working Memory Test-Part 1, a cross-modal mental manipulation task where patients hear digits, but respond by touching digits from lowest to highest on an answer key. Only 4 and 5-span trials were analyzed. Using an iPad, all test stimuli were played; and, all responses were obtained with a touch key. Only correct trials were analyzed. Average time to complete trials and latency for each digit was recorded. Results: Groups did not differ when average time to complete 4-span trials was calculated. MCI patients displayed slower latency, or required more time to re-order the 1st and 3rd digits. Regression analyses, primarily involving initial and latter response latencies, were associated with better, but different underlying neuropsychological abilities. Almost no 5-span analyses were significant. Conclusions: This cross-modal test paradigm found no difference for total average time. MCI patients generated slower 1st and 3rd response latency, suggesting differences in time allocation to achieve correct serial order recall. Moreover, different neuropsychological abilities were associated with different time-based test components. These data extend prior findings using a standard backward digit span test. Differences in time epochs are consistent with constructs underlying the model of executive attention and help explain mental manipulation deficits in MCI. These latency measures could constitute neurocognitive biomarkers that track emergent disease.